Pengaruh Pengendalian Internal dan Kecerdasan Spiritual terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa di Kec. Buliyohuto - Mardlia A. Buato; Niswatin; Amir Lukum (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Study This aim For analyze Influence Internal Control and Spiritual Intelligence Prevention Fraud in Village Fund Management in the District Boliyohuto. Deep method study This use approach quantitative. Data used in study This is the primary data obtained with spread questionnaire to device villages in the District Boliyohuto . Amount sample in study This amounting to 78 respondents. Deep data analysis study This use analysis multiple linear regression. Research result This show that Internal Control and Spiritual Intelligence have an influence in a way partial and simultaneous to Prevention Fraud. Coefficient in study This of 30.7% which is significant variable Prevention Fraud in study This explained by variables Internal Control and variables Spiritual Intelligence is 30.7%.